Traffic Management Effectivity of Bulak Kapal Underpass Development, Bekasi Indonesia - Yola Rachmadina; Andri Irfan Rifai; Susanty Handayani (International Journal Labs, 2022)
Crossroads are one of the places that become a source of congestion. One of the intersections that are a source of congestion in Bekasi is the Bulak Kapal Intersection. This study aims to analyze the effectiveness of traffic management in the Bulak Kapal Underpass. The data collection method was carried out by distributing questionnaires offline and online. Data processing from respondents' questionnaire answers is presented using a spider chart with Microsoft Excel tools. The results showed that eleven parameter assessments before the Underpass was built and after the Underpass was built experienced an increase. The three parameters with the highest gap values or parameters that share a significant increase are traffic density, vehicle speed, and comfort. Meanwhile, the three parameters with the lowest gap values are road condition parameters, road completeness, and environmental friendliness.